The effect of natural fillers on the marine biodegradation behaviour of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) - Meereboer, Kjeld W. (Sci Rep, 2021)
Worldwide, improper disposal of plastics is instigating environmental initiatives to combat plastics accumulation of in the environment and the world’s oceans. Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) biocomposites with Miscanthus (Misc) fibres and distillers’ dried grains with solubles (DDGS) were studied to ascertain if natural fibres and proteinaceous fillers can improve polyhydroxyalkanoate marine biodegradability. Using ASTM standard D7991-15, the biodegradation of PHBV, PHBV with Misc (15 and 25 wt%) and PHBV with DDGS (15 and 25 wt%) was performed in a simulated marine environment for the first time, as indicated by a literature survey. PHBV/Misc (85/15) and (75/25) biocomposites showed 15 and 25% more biodegradation compared to PHBV, respectively. Proteinaceous PHBV/DDGS (85/15) and (75/25) biocomposites showed 17 and 40% more biodegradation compared to PHBV, respectively. Furthermore, PHBV/Misc (75/25) and PHBV/DDGS (75/25) biocomposites were marine biodegraded in 412 and 295 days, respectively. In conclusion, proteinaceous fillers (DDGS) biocomposites have better marine biodegradability than miscanthus.